2002
DOI: 10.1055/s-2002-26689
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Venous Drainage in Complex Congenital Cardiac Surgery

Abstract: Here, we report on a case of temporary neurological damage following conduit replacement from the right ventricle to pulmonary artery during which vacuum-assisted venous drainage was used. We will discuss the benefits and risks of this technique with potential arterial air embolism despite the use of arterial line filters. We will also make recommendations for avoiding such complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Concerns have been expressed about the exacerbation of arterial air embolism owing to entrainment of air in the venous system [Davila 2001;Carrier 2002;Walther 2002], but other authors have not experienced this as a problem. Carrier et al [2002] showed that vacuum-assisted venous drainage does not significantly increase air microembolism and was not associated with increased neurological risk following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns have been expressed about the exacerbation of arterial air embolism owing to entrainment of air in the venous system [Davila 2001;Carrier 2002;Walther 2002], but other authors have not experienced this as a problem. Carrier et al [2002] showed that vacuum-assisted venous drainage does not significantly increase air microembolism and was not associated with increased neurological risk following surgery.…”
Section: Introductionmentioning
confidence: 99%